Family Interpersonal Communication Patterns in Reducing The Numbers of Free Sex - Aulia Rahman; Fatra Indira Deni (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
As social beings, they are very important elements in human life, based on human communication relationships, they can also meet physical and spiritual needs. Communication is a direct or indirect contact relationship either individually or in groups. The purpose of this study was to determine and describe the pattern of interpersonal communication in the family to reduce the number of free sex. From the results of the research that has been done, it can be stated that the communication patterns carried out by several families in the Bandar Selamat environment are very intense but less useful, so they still need guidance from related parties so that interpersonal communication patterns in the family to reduce the number of free sex can run well.